Simulation the impact of eco expenditure on the effectiveness of eco projects: The railways of Ukraine case - Shpak, Nestor; Maznyk, Liana; Dvulit, Zoriana; Mykytiuk, Oksana; Melnyk, Tatiana (My University, 2021)
A system of indicators of the structure and dynamics of operational freight turnover, which includes environmental protection expenditure, carbon dioxide (СО2) emissions from railway transport enterprises was created. A multilevel hierarchical model of the relationship between: operational turnover and the amount of СО2 emissions by the relevant sources of pollution in terms of their volume and structure (the first level); environmental expenditure and the amount of СО2 emissions (the second level), was developed. The results of the study confirmed that largely the reduction of such harmful emissions is due to the size and structure of expenditure for environmental projects. The novelty of the article is the development of methodological approaches to test the hypothesis that with increasing environmental expenditure for environmental protection, СО2 emissions from rolling stock and stationary sources of pollution of the six railways of Ukraine are reduced.
Keywords: expenditure; environmental protection; Ukrainian railways; simulation; витрати; охорона навколишнього середовища; українська залізниця; моделювання; кафедра економіки праці та менеджменту